The Effect of Brand Awareness on Marketing Performance with Brand Trust mediation on Infogarut clients: Non-Culinary - Kustiani, Neng Ratih; Setiawan, Rahyuniati; Mubarok, Teten Mohamad Sapril (Institut Agama Islam Negeri Kendari, 2025)
This study aims to analyze the effect of Brand Awareness on Marketing Performance with the mediating role of Brand Trust on Infogarut's non culinary clients. The background of this research is based on the importance of brand awareness in shaping customer trust and increasing the effectiveness of marketing strategies, especially in MSMEs that utilize local digital platforms. This research uses a quantitative approach with Structural Equation Modeling (SEM) analysis techniques through SmartPLS 3.0 software. The sample consisted of 179 respondents who used Infogarut advertising services in the non-culinary sector. The results showed that Brand Awareness has a positive and significant effect on Brand Trust and Marketing Performance. Brand Trust is also proven to have a significant influence on Marketing Performance and mediate the relationship between Brand Awareness and Marketing Performance. The R-square values are 0.924 and 0.814 respectively, with a Q-square of 0.711, indicating the model has high predictive power. The findings provide practical and theoretical contributions in the development of brand trust-based marketing strategies.